MiR-25 Promotes Cell Proliferation, Migration, and Invasion of Non-Small-Cell Lung Cancer by Targeting the LATS2/YAP Signaling Pathway. (18th June 2019) - Wu, Tangwei; Hu, Hui; Zhang, Tianzhu; Jiang, Liyuan; Li, Xiaoyi; Liu, Shuiyi; Zheng, Chao; Yan, Ge; Chen, Weiqun; Ning, Yong; Li, Yong; Lu, Zhongxin
Abstract : Metastasis is the leading cause of high mortality in lung cancer patients, and metastatic lung cancer is difficult to treat. miRNAs are involved in various biological processes of cancer, including metastasis. Our previous studies revealed that miR-25 promoted non-small-cell lung cancer (NSCLC) cell proliferation and suppressed cell apoptosis by directly targeting TP53 and MOAP1 . In this work, we further explored the miR-25 expression in NSCLC patients in the Cancer Genome Atlas (TCGA) database and measured the miR-25 expression levels in the tissues of NSCLC patients and cell lines. miR-25 was overexpressed in both NSCLC tissues and cell lines. NSCLC patients who expressed a higher level of miR-25 exhibited worse overall survival than those with a lower level of miR-25. Overexpression of miR-25 enhanced NSCLC cell migration and invasion, while the inhibition of miR-25 exhibited the opposite effects. We identified the large tumor suppressor homology 2 ( LATS2 ) as a new target gene of miR-25 in lung cancer. The effects of miR-25 on promoting NSCLC cell migration and invasion were at least partially due to activation of the Hippo signaling pathway. Additionally, miR-25 antagomir inhibited xenograft tumor growth and metastasis by the upregulation of LATS2. Taken together, our findings demonstrate that miR-25 contribute to lung cancer cell proliferation and metastasis by targeting the LATS2/YAP signaling pathway, which implicate miR-25 as a promising therapeutic target for lung cancer metastasis. Given that oxidative stress induces the overexpression of miR-25 and plays a critical role in cancer progression, this study establishes miR-25 as an intermediate between oxidative stress and lung cancer metastasis.